MOLECULAR DIAGNOSIS OF PROSTHETIC JOINT INFECTION. A REVIEW OF EVIDENCE - Gallo, Jiří; Raška, Milan; Dendis, Miloš; Florschütz, Anthony V.; Kolář, Milan (Biomedical papers, 2004)
Prosthetic joint infection (PJI) diagnosis includes several classes of verification. Among them, only a few have a stronger independent value, namely intraarticular purulence and communicating fistulas. Other diagnostic methods require careful test combinations, analysis, and interpretation. Molecular based techniques using the polymerase chain reaction (PCR) seem to be a promising PJI diagnostic modality due to its excellent sensitivity, specificity, positive predictive value, and speed. Most of the recent reviewers are in agreement that molecular diagnosis has enough potential for future application in orthopaedics even if there are only a few heterogeneous studies fully supporting this concept. Conversely, at least one study has been published with significantly worse results (sensitivity and specificity less than 0.75). The lack of supporting evidence in the published studies may be closely related to varying PCR laboratory procedures, inappropriate reference standards, and other methodological shortcomings among research centers. It is not yet justifiable to firmly include molecular methods into the present PJI diagnostic schemes. The orthopaedic community must await the results of well-organized ongoing studies before considering inclusion of molecular diagnostics as a PJI diagnostic method. The aim of this paper was to make a survey of current PJI molecular diagnostic techniques in orhopaedics.
Keywords: Prosthetic joint infection/Molecular diagnosis/PCR technique/Total joint arthroplasty/Complications/Review